The effects of cycloheximide on the biosynthesis and secretion of proteoglycans by chondrocytes in culture. - Mitchell, D (1981)
Proteoglycans synthesized by rat chondrosarcoma cells in culture are secreted into the culture medium through a pericellular matrix. The appearance of [35S]sulphate in secreted proteoglycan after a 5 min pulse was rapid (half-time, t 1/2 less than 10 min), but that of [3H]serine into proteoglycan measured after a 15 min pulse was much slower (t 1/2 120 min). The incorporation of [3H]serine into secreted protein was immediately inhibited by 1 mM-cycloheximide, but the incorporation of [35S]sulphate into proteoglycans was only inhibited gradually(t 1/2 79 min), suggesting the presence of a large intracellular pool of proteoglycan that did not carry sulphated glycosaminoglycans. Cultures were pulsed with [3H]serine and [35S]sulphate and chased for up to 6 h in the presence of 1 mM-cycloheximide. Analysis showed that cycloheximide-chased cells secreted less than 50% of the [3H]serine in proteoglycan of control cultures and the rate of incorporation into secreted proteoglycan was decreased (from t 1/2 120 min to t 1/2 80 min). Under these conditions cycloheximide interfered with the flow of proteoglycan protein core along the route of intracellular synthesis leading to secretion, as well as inhibiting further protein core synthesis. The results suggested that the newly synthesized protein core of proteoglycan passes through an intracellular pool for about 70-90 min before the chondroitin sulphate chains are synthesized on it, and it is then rapidly secreted from the cell. Proteoglycan produced by cultures incubated in the presence of cycloheximide and labelled with [35S]sulphate showed an increase with time of both the average proteoglycan size and the length of the constituent chondroitin sulphate chain. However, the proportion of synthesized proteoglycans able to form stable aggregates did not alter.